2013
DOI: 10.1515/znc-2013-11-1210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Oxidative Stress Response of a Cytochrome P450 Gene (CYP4G11) from Apis cerana cerana

Abstract: Cytochrome P450 proteins, widely distributed multifunctional enzymes, are mainly involved in biosynthetic and degradative pathways of endogenous compounds and the detoxifi cation of xenobiotics in insects. Moreover, these enzymes exhibit peroxidase-like activity, therefore they may be involved in protecting organisms against the toxicity of reactive oxygen species (ROS). In the present study, we cloned a CYP4G11 gene -AccCYP4G11 -from the Chinese honey-bee (Apis cerana cerana). The open reading frame of the cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Currently, this topic has become a major focus and has led to widespread efforts to understand the molecular basis that underlies insecticide resistance. Previous researches identified and characterized several P450 genes and verified that those P450 genes responded to insecticide detoxification in A. c. cerana (Shi et al, 2013; Zhang et al, 2018). In this study, four novel P450 genes were identified and characterized.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Currently, this topic has become a major focus and has led to widespread efforts to understand the molecular basis that underlies insecticide resistance. Previous researches identified and characterized several P450 genes and verified that those P450 genes responded to insecticide detoxification in A. c. cerana (Shi et al, 2013; Zhang et al, 2018). In this study, four novel P450 genes were identified and characterized.…”
Section: Introductionmentioning
confidence: 84%
“…In resistant Anopheles mosquitoes , the two P450 enzymes, CYP4G16 and CYP4G17 , are frequently overexpressed and particularly highly enriched in the abdominal integument (Ingham et al, 2014). Early studies provided evidence that the CYP4G11 gene plays an important role in protecting honeybees from insecticide (phoxim, paraquat, decamethrin) damage (Shi et al, 2013). The P450s in the honeybee genome play a crucial role in the detoxification of phytochemicals and pesticides in the diet (nectar, honey, and pollen) of both larval and adult stages (Mao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In many insects, P450s play important roles in detoxification, including endogenous and exogenous agents (Shen et al ., 2003; Sasabe et al ., 2004; Kirischian and Wilson, 2012). However, only a few P450s genes from A. c. cerana have been reported (Shi et al ., 2013; Zhu et al ., 2016; Zhang et al ., 2018). Therefore, the identification and characterization of new P450s genes have become very attractive research areas.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies by Shi et al . (2013) provided evidence that the CYP4G11 gene was involved in protecting honeybee workers from abiotic stress damage. Several CYP4 genes are overexpressed in the pesticide-resistant Culex pipiens , Diabrotica virgifera , and Helicoverpa armigera species (Pittendrigh et al ., 1997; Scharf et al ., 2001; Shen et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation